ADAPTATION PROCEDURE OF THE TEST OF ASSERTIVE BEHAVIOUR - Makarevičs, Valērijs; Iliško, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The problem of assertiveness as a condition of self-actualization is actively developed by both, theorists and practitioners. In order to explore it, more than 30 different tests are being developed by the scientists. However, most of them have common drawback.In reality, behavioural acts that in one cultural environment are perceived as manifestations of assertiveness, in other context it can be interpreted as aggression or perceived as completely unacceptable. The purpose of this study was to select an assertiveness test created in a similar culture, translate it into Latvian and test for reliability. Both, direct and reverse translation was carried out, which was discussed with the author of the test. Repeated pilot testing indicate to high reliability of a translated version of the test.